Developmental Dynamics of Radial Vulnerability in the Cerebral Compartments in Preterm Infants and Neonates - Kostović, Ivica; Kostović-Srzentić, Mirna; Benjak, Vesna; Jovanov-Milošević, Nataša; Radoš, Milan (Frontiers in Neurology, 2014)
The developmental vulnerability of different classes of axonal pathways in preterm white matter is not known. We propose that laminar compartments of the developing cerebral wall serve as spatial framework for axonal growth and evaluate potential of anatomical landmarks for understanding reorganization of the cerebral wall after perinatal lesions. The 3-T MRI (in vivo) and histological analysis were performed in a series of cases ranging from 22 postconceptional weeks to 3 years. For the follow-up scans, three groups of children (control, normotypic, and preterms with lesions) were examined at the term equivalent age and after the first year of life. MRI and histological abnormalities were analyzed in the following compartments: (a) periventricular, with periventricular fiber system; (b) intermediate, with periventricular crossroads, sagittal strata, and centrum semiovale; (c) superficial, composed of gyral white matter, subplate, and cortical plate. Vulnerability of thalamocortical pathways within the crossroads and sagittal strata seems to be characteristic for early preterms, while vulnerability of long association pathways in the centrum semiovale seems to be predominant feature of late preterms. The structural indicator of the lesion of the long association pathways is the loss of delineation between centrum semiovale and subplate remnant, which is possible substrate of the diffuse periventricular leukomalacia. The enhanced difference in MR signal intensity of centrum semiovale and subplate remnant, observed in damaged children after first year, we interpret as structural plasticity of intact short cortico-cortical fibers, which grow postnatally through U-zones and enter the cortex through the subplate remnant. Our findings indicate that radial distribution of MRI signal abnormalities in the cerebral compartments may be related to lesion of different classes of axonal pathways and have prognostic value for predicting the likely outcome of prenatal and perinatal lesions.